Peran Kepuasan Memediasi Pengaruh Tunjangan Kinerja Terhadap Kinerja Perangkat Desa Se-Kecamatan Abiansemal - Pradnya Wati, I Gusti Ayu Sri; Adisti Abiyoga Wulandari, Ni Luh; Suputra, Gusti Alit (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2021)
The village is the smallest legal community unit. To run the Village administration, Village officials are needed. The purpose of this study was to determine how the effect of performance allowances on job satisfaction, the effect of providing performance allowances on performance, the effect of job satisfaction with the performance of village apparatus and the role of satisfaction mediating the effect of performance allowances on performance in village apparatus in Abiansemal District. The number of respondents taken was 73 people. The data analysis technique used is the validity and reliability test, path analysis (Path Analysis), and the mediation test (Sobel). Based on the research results, it was found that the performance allowance has a positive and significant effect on job satisfaction. Performance allowances have a positive and significant effect on performance. There is a significant influence between job satisfaction on performance. Job satisfaction mediates the role of performance benefits on performance.